Knowledge discovery using web bags in a web warehouse - LIM, Ee Peng (Institutional Knowledge at Singapore Management University, 2000)
Sets and bags are closely related structures. A bag is different from a set in that it is sensitive to the number of times an element occurs while a set is not. In this paper, we introduce the concept of web bag in a web warehouse as a part of our the WHOWEDA project. Informally, a web bag is a web table which allows multiple occurrences of identical web tuples. Web bag helps to discover useful knowledge from a web table such as visible documents (or web sites), luminous documents and luminous paths. We formally discuss the semantics and properties of web bags, and illustrate with examples applications of web bag in knowledge discovery in a web warehouse.